The effectiveness of corporate downsizing as a cost reduction strategy: a case of Zimbabwe Commercial banks - Maenzanise, Lewis Shingirai (2020)
The research was carried out to investigate the effectiveness of corporate downsizing as a cost reduction strategy, a case of Zimbabwe commercial banks. The objectives of the study was to evaluate the effectiveness of downsizing as a cost reduction strategy, to determine factors to be considered when implementing downsizing, to assess the effect of implementing downsizing strategy on performance and to establish the measures to be adopted to ensure effective implementation of downsizing. The study applied descriptive research design. The target population was the managers of commercial banks and employees in Harare. Banks.. The sample consisted of fifty-five respondents. The respondents were all from commercial banks branches and departments in Harare. Instruments used were questionnaires and interviews. Fifty-five questionnaires were administered and 73% of them were returned. Seven interviews were also carried with the management and employees. The major findings indicated that downsizing has led to a reduction of costs due to the reduced payroll costs and overtime bans but it has led to jeopardized operational performance, the process has led to overburdened staff with very high workloads and it has compromised the productivity of employees. The researcher came up with the conclusion that though the operating costs were reduced, downsizing has led to insecure employees and demotivated staff with high workloads. Lack of effective communication between the management and the employees as to the cost strategies was seen by the researcher as a reason for the compromised productivity of the employees. The major recommendations were that management should not solely concentrate on reducing costs but should also consider the welfare of the employees as well as the long term goals of the organization. Management should assure the remaining staff of their jobs and should restructure the duties and responsibilities of employees to match with the remaining staff so as to reduce the problem of heavy workloads on employees.